Urgensi Metode Ceramah dan Diskusi (Buzz Group) dalam Proses Pembelajaran di Madrasah - Mansir, Firman (State Islamic Institute of Madura, 2020)
This research describes about the importance of lecture-discussion method in studying at Madrasa. Good education can lead students to achieve good outcome by using and prepare effective methods and having perfect teaching materials in order to achieve dynamic learning goals. This research aimed to achieve the effectiveness of learning that has been taught in order to facilitate students to obtain information about taught materials. Professional teachers professionals need to understand very well about how to do good learning. In addition, educators certainly have good teaching skills before assuming the task of educator. The skills of an educator are obtained from various training and learning experiences. Teaching strategies and methods are a component contained in the learning system, the components are: learning objectives, teaching materials, students, time and educators. Therefore, lecture-discussion method of buzz group is effective to use as learning method at Madrasa.